Influence of motivation on the perception of mathematics by secondary school students - Hossein-Mohand, Hassan; Hossein-Mohand, Hossein (Frontiers in Psychology, 2023)
Motivation, the teacher-student relationship, the use of resources and the time spent studying, in addition to the family economic and social context, are some of the factors that affect academic performance and directly influence school failure. This paper evaluates the motivation in mathematics students’ performance, by analyzing indicators of the mathematics learning dimension. A total of 2018 secondary students were evaluated in this cross-sectional study. Motivation, teaching, resources, and study time were analyzed with a validated 20-item questionnaire. Statistical analysis revealed that student motivation appears significantly related to the perception of teaching practice and the use of resources for study. Students with high motivation have a positive perception of teaching practice. Gender differences were not observed. In addition, the motivation indicator allows grouping students into various motivational profiles.